Low-Pofile beam-steerable microstrip antenna with metamaterial - Amit Mehta (2017 IEEE International Symposium on Antennas and Propagation & USNC/URSI National Radio Science Meeting, 2017)
A novel microstrip antenna is presented for beam steering applications for 2.45 GHz (802.11b/g/n) WiFi band. The antenna consists of four L-shaped microstrips. Each L-shaped strip is fed by a vertical probe which is connected to a stepped transmission line impedance matching strip and other end of the matching strip is connected to a standard 50 Ω SMA (Subminiature version A) port. The matching strip layer is placed on the reverse side of the ground layer. In addition, an EBG (Electromagnetic Band Gap) structure is implemented between the radiating strips layer and ground layer to improve the gain (8.61 dBi) of the antenna. The total height of the antenna is 3.52mm (≈λ0/35°, where λ0 is free space wavelength at 2.45 GHz). When any of the four ports is excited one at a time and remaining ports are open circuited, the antenna provides a tilted beam of θmax=35° directing away from the corner of the L-shaped strip. Thus, by switching the excitation among four ports using a SP4T RF switch the antenna can maneuver its radiation beam in four different space quadrants of φmax =55°, φmax =145°, φmax =235° and φmax =325° in azimuth plane.